1983
DOI: 10.1038/jcbfm.1983.9
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Serotonin on Local Cerebral Blood Flow

Abstract: Summary: This study was undertaken to measure the effects of serotonin administration on local cerebral blood flow following blood -brain barrier (BBB) disruption with hypertonic urea, Rats were anesthetized with halo thane in nitrous oxide and oxygen (70%:30%). In some animals urea (3.5 M) was infused retrogradely through an external carotid catheter, followed after 10 min by serotonin (50 ng kg

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…The flow values in both groups of animals with hypotension at the lower limt of autoregulation for halothane anaesthetised rats (groups 1 and 2) are on average 12% less than those previously reported by Tamura et al 5 from our laboratory, but are slightly higher than a series of normal values reported more recently. 35 This suggests that with this degree of hypotension, in both our groups there was a trend towards reduced flow, although not of sufficient magnitude to reach statistical significance. This adds weight to the argument that the level of hypotension selected (40-50 mmHg) is at the lower limit of autoregulation.…”
Section: Discussionmentioning
confidence: 87%
“…The flow values in both groups of animals with hypotension at the lower limt of autoregulation for halothane anaesthetised rats (groups 1 and 2) are on average 12% less than those previously reported by Tamura et al 5 from our laboratory, but are slightly higher than a series of normal values reported more recently. 35 This suggests that with this degree of hypotension, in both our groups there was a trend towards reduced flow, although not of sufficient magnitude to reach statistical significance. This adds weight to the argument that the level of hypotension selected (40-50 mmHg) is at the lower limit of autoregulation.…”
Section: Discussionmentioning
confidence: 87%
“…38 ' 42 - 45 For example, when the BBB is artifically perturbed, widespread reductions in 1CBF have been documented with serotonin infusion. 42 " 44 The elevated levels of plasma serotonin reported in the present study might therefore be expected to produce alterations in 1CBF if BBB dysfunction occurs after CCA thrombosis. In this regard, studies have demonstrated both BBB breakdown and alterations in 1CBF immediately after photochemically induced CCA thrombosis.…”
Section: Discussionmentioning
confidence: 96%
“…Important general properties include a lack of antinociceptive effects (123) and good experimental evidence that sumatriptan does not readily cross the blood-brain barrier in animals (124)(125)(126). No data on humans are available and it is possible that functional properties of the blood-brain barrier may alter during a migraine attack (27,28). Rare, but sometimes prominent side effects such as transient drowsiness, sedation, dizziness, vertigo and fatigue may point to some central effects of sumatriptan during an attack (102,127).…”
Section: Sumatriptanmentioning
confidence: 99%
“…Vasodilation is mediated directly via vascular smooth muscle and indirectly via the release of endothelial derived relaxing factor and presynaptic inhibition of release of NA from vascular sympathetic adrenergic nerve terminals (20). Vasoconstriction appears to be mediated via 5-HT 2 receptors in peripheral blood vessels and via 5-HT 1 -like, presumably 5-HT 1d , receptors in the cranial vasculature (21-26), Infusion of 5-HT in baboons caused constriction of the ipsilateral internal carotid artery without change in rCBF, presumably because 5-HT does not cross the blood-brain barrier (27,28). Microapplication of 5-HT in situ caused dilation of cerebral arterioles with a diameter of less than 70 µmol, which can be blocked by propranolol, and constriction of larger cerebral arteries with a diameter greater than 200 µmol (29), which can be blocked by the universal 5-HT receptor blocker methysergide (30) and the 5-HT 2 receptor antagonist ketanserin (31).Interesting links between the central and peripheral vascular 5-HT systems are suggested by the observations that 5-HT nerve fibers originating from the raphe nuclei innervate pial vessels (32-34) and that activation of nucleus raphe dorsalis in the monkey increases CBF about 20% via a facial nerve pathway (35).…”
mentioning
confidence: 99%